WORKSHOP PEMBUATAN MEDIA PEMBELAJARAN BIOLOGI BERBANTUAN KOMPUTER TENTANG PENGOLAHAN SAMPAH ORGANIK SEKOLAH DENGAN METODE ALAMI - Mariyam, Siti (Universitas Negeri Yogyakarta, 2010)
Decaying process of organic garbages causes environment quality decreasing. The technology is needed for organic garbage management in order to avoid environment pollution. The teachers have a strategic role in dissemination of knowledge and technology to the students and the society. The problems were how to increase knowledge of the teachers about organic garbage management, especially organic school garbage management, and how to develop the competency of the biology teachers in composing of biology lessoning media based on computer about natural method of organic school garbage treatment. Some activities held to solve the problems were: interactive speech about garbage and environment problems caused by garbages, practice of organic garbage composting, and practice of composing of biology lessoning media based on computer about natural method of organic school garbage treatment. The activities were success to increase knowledge and skill of the biology teachers in organic garbage management, which of the post-test scores were higher then the pre-test scores. According to the result of the evaluation, the CDs of lessoning media made by the teachers were suitable to the basic competency